Investigating the impact of atmosphere–wave–ocean interactions on a Mediterranean tropical-like cyclone - Varlas, G.; Vervatis, V.; Spyrou, C.; Papadopoulou, E.; Papadopoulos, A.; Katsafados, P. (2020)
Understanding the governing mechanisms of atmosphere–wave–ocean​ interactions is critical for unravelling the formation and evolution mechanisms of severe weather phenomena. This study aims at investigating the effects of atmosphere–wave–ocean​ feedbacks on a Mediterranean tropical-like cyclone (medicane), occurred on 27–30 September 2018 at the central-eastern Mediterranean Sea and characterized by severe environmental and socioeconomic impact. To unveil the interactions across the air–sea interface, the medicane was simulated by an integrated modelling system consisting of the Chemical Hydrological Atmospheric Ocean wave System (CHAOS), upgraded by embedding to it the Nucleus for European Modelling of the Ocean (NEMO) as ocean circulation component. Coupled simulations revealed that air–seaheat transfer and Ekman pumping, bringing sub-surface cold waters in upper ocean layers (upwelling), caused SST cooling (∼2–3 °C). SST cooling triggered a negative feedback loop procedure tending to balance between atmospheric and ocean processes. It also attenuated the cyclone and, subsequently, reduced the atmospheric energy embedded in ocean through the upper ocean vertical stratification weakening, thus, upper ocean vertical mixing, upwelling and SST cooling. The waves adjusted this feedback loop making the system more resistant in air–sea flux variations. Waves additionally weakened the cyclone not only due to the kinetic energy loss in the lower-atmosphere but also due to the enhancement of SST cooling which is attributed to the strengthening of Ekman pumping and vertical mixing, forced by wind stress increase. Nevertheless, waves partially balanced the air–wave–sea exchanges through the slight enthalpy flux gain under high wind conditions which is explained by considering the increase of enthalpy transfer coefficient in rougher sea areas.
Keywords: Air–sea interaction; CHAOS system; Coupled models; Enthalpy; Medicane; Momentum; Nemo; WAM; WRF